Strengthening Africa’s pastoral food systems transformation in the face of climate change - Banerjee, Rupsha R. (2022)
This short interview with ILRI’s drought-risk finance specialist, Rupsha Banerjee, describes how sustainable pastoralism can contribute to Africa’s food systems transformation. It was presented at the 2022 African Green Revolution Forum as part of a special livestock focused event called 'The cow in the room – the role milk, meat, and eggs play in sustainable food systems transformation'.